A novel low-temperature mashing schedule for brewing with unmalted sorghum: optimisation - Holmes, C.P.; Casey, J.; Cook, David J. (Fachverlag Hans Carl GmbH, 2017)
Laboratory mashing experiments were used to investigate and optimise protocols for mashing with unmalted sorghum using a novel low-temperature (Tmax = 78 °C) enzyme blend and mash schedule. Results are compared with equivalent data for a traditional high-temperature mash schedule (Tmax = 95 °C). An experimental design approach was used to model wort quality (Extract, FAN content, filtration rate, fermentable sugars contents, colour and turbidity) produced by each mash schedule across a full factorial design space. The factors varied were 1. Mash-in pH (5.5 ± 0.25) 2. Calcium chloride addition (2 g/kg ± 1) 3. Potassium metabisulphite (KMS) addition (1 g/kg ± 1) and 4. The amount of enzyme blend added to each system (recommended dosage ± 50%). Wort quality was particularly sensitive to mash-in pH with best results achieved close to pH 5.5 (hence selected as the design centre point). At pH values below 5.5 wort extract decreased with either schedule, whereas the impacts of elevated pH at mash-in were slightly higher wort FAN levels, but increased wort turbidity and colour and reduced filterability of the laboratory wort. The novel low temperature mash schedule was able to produce wort of comparable quality with that from the high-temperature schedule. Design space models for the high- and low-temperature mash systems were used to suggest optimal conditions for each varied factor, with the objective of maximising wort extract and FAN, whilst minimising enzyme addition rates (hence cost). Optimised extracts of 10.6 and 10.8 °P were achieved for the low and high-temperature mash systems, with FAN levels of 60 and 57.2 mg/L respectively. Optimal conditions required a mash-in pH of 5.75 and around 2 g/kg KMS in each case. The high-temperature system required around 3 g/kg CaCl2 addition for optimal performance whereas the low-temperature mash performed well with just 1 g/kg added CaCl2. Use of the novel low-temperature mash schedule should facilitate substantial energy savings in the brewery, because it operates at lower maximum temperatures for a shorter overall process time and also because the mash schedule features only increases in process temperatures with time. This saves on the energy required to cool the mash in the traditional process from 95 °C (for starch gelatinisation) to the saccharification enzyme stand (60 °C).